Transnational Criminal Law in Transatlantic Perspective (1870–1945): Introductory Notes, Initial Results and Concepts - Karl Härter; Valeria Vegh Weis (Rechtsgeschichte - Legal History)
The article outlines the scope and concepts of the research project »Transnational Criminal Law in Transatlantic Perspective (1870–1945)« and introduces the respective case studies of the Focus. Although research has studied the history of crime, criminal justice, policing and punishment in Latin America, the transatlantic dimension of transnational criminal law has still to be explored by legal history. This could be achieved by applying the concepts of »historical regimes of normativity« and »global legal history« integrating as well approaches of »critical criminology« and »criminal selectivity«. This conceptional framework allows to study the transatlantic dimension of transnational crime, norms, discourses and practices as the formation of a transnational regime. In this regime not only states but also non-governmental actors from the Global North and the Global South played a vital role, exchanged and created legal knowledge and normativity as well as narratives of »international crime« which also had an impact on the respective domestic levels of criminal law, criminalisation, policing and criminal justice. In this regard, research on the formation of transnational-transatlantic criminal law regimes could gain new insights in the legal history of criminal law as well as to current issues of the global governance of crime.